Um estudo sobre Política Científica, Tecnológica e de Inovação emMinas Gerais: análise do Programa de Incentivo à Inovação sob aótica dos seus stakeholders - Samara Lopes Barbosa (2012)
Innovation is actually an obligatory subject in political agendas across the world. In the same way, politics that foster and encourage innovation has become frequent in discussions about economic growth and development. Thus, this work was born from a general interest about Politics in Science and Technology and its actions in Minas Gerais, more specifically, the Innovation Incentive Program (IIP). Like many countries,Brazil uses a mix of instruments to support R&D in the private sector. This mix includes tax incentives (indirect support) and subsidies (direct support). Those incentives are created to increase private spending and promote the competitiveness and productivity of the economy. Under state policies, IIP is a program with direct support, designed by State Secretariat of Science, Technology and Higher Education of MinasGerais (Sectes) in partnership with Brazilian Service of Support for Micro and Small Enterprises in Minas Gerais (SEBRAE-MG). Politics in Science and Technology aims to use the technological capacity of universities together with economic sectors, seeking mutual benefits for the local economy. Due to impact that politics can have on society, evaluation of its programs, such as IIP, it is important to public management, thereby itmay contribute to improve its results. The traditional studies of evaluation of public politics are often based on quantitative methods, and because of this, it is often being forced to be limited to a small number of explanatory variables, due to technical and organizational difficulties. Seeking another look, this research, a qualitative, will utilize the concepts of discourse in organizations to analyze the effectiveness of the actions ofthe Innovation Incentive Program, from the perspective of its stakeholders.